2013
DOI: 10.3390/d5030627
|View full text |Cite
|
Sign up to set email alerts
|

Untangling the Genetic Basis of Fibrolytic Specialization by Lachnospiraceae and Ruminococcaceae in Diverse Gut Communities

Abstract: Abstract:The Lachnospiraceae and Ruminococcaceae are two of the most abundant families from the order Clostridiales found in the mammalian gut environment, and have been associated with the maintenance of gut health. While they are both diverse groups, they share a common role as active plant degraders. By comparing the genomes of the Lachnospiraceae and Ruminococcaceae with the Clostridiaceae, a more commonly free-living group, we identify key carbohydrate-active enzymes, sugar transport mechanisms, and metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

26
617
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 796 publications
(644 citation statements)
references
References 38 publications
26
617
1
Order By: Relevance
“…Together, the relative abundance of these organisms comprised more than half of the abundance in the deep layer and more than a third in the middle soil layer. Research by others has shown that members from all three of these taxa are capable of degrading lignocellulosic biomass (Bhalla et al, 2013;Biddle et al, 2013;Vital et al, 2014;Zainudin et al, 2013) and that many strains are rich in glycoside hydrolases (Bhalla et al, 2013;Biddle et al, 2013).…”
Section: Discussionmentioning
confidence: 96%
“…Together, the relative abundance of these organisms comprised more than half of the abundance in the deep layer and more than a third in the middle soil layer. Research by others has shown that members from all three of these taxa are capable of degrading lignocellulosic biomass (Bhalla et al, 2013;Biddle et al, 2013;Vital et al, 2014;Zainudin et al, 2013) and that many strains are rich in glycoside hydrolases (Bhalla et al, 2013;Biddle et al, 2013).…”
Section: Discussionmentioning
confidence: 96%
“…3E). Among these bacteria, Ruminococcaceae and Lactobacillus have been reported to be commensal bacterial in the periodontium or gastrointestinal tract (Szkaradkiewicz et al 2011;Biddle et al 2013). Bacillus, Staphylococcus, Prevotella, Pseudomonas, Acinetobacter, Fusobacterium, and Porphyromonas have been reported to have pathogenic potential in the periodontium and gut (Szkaradkiewicz et al 2011;Hajishengallis 2014;Rolny et al 2014;Souto et al 2014).…”
Section: Aging Increases Colonization Of P Gingivalis and Reduces Bamentioning
confidence: 99%
“…Clostridium are active cellulolytic bacteria that play a crucial role in the decomposition of lignocellulosic substrates under anaerobic conditions, e.g., in the digestive system of cattle 28 and in AD processes operated upon cellulosic wastes using their efficient cell-bound cellulosomal systems. 29 The enrichment of Clostridium has been reported in various LMCs isolated from cellulolytic seed cultures from different sources.…”
mentioning
confidence: 99%